Pengaruh Capital Intensity, Sales Growth, Kepemilikan Institusional Terhadap Tax Avoidance Pada Perusahaan Manufaktur Yang Terdaftar Pada Bursa Efek Indonesia Periode 2016 – 2019 - Iqbal Iqbal; Desy Astrid Anindya; Aditya Amanda Pane (Jurnal Ilmiah Akuntansi Keuangan dan Bisnis (JIKABI), 2022)
This study aims to determine whether capital intensity, sales growth, and institutional ownership have an effect on tax avoidance in manufacturing companies listed on the Indonesia Stock Exchange. This type of research is causal associative. The population in this study were 120 manufacturing companies. This study uses purposive sampling as a sampling technique with certain criteria, and obtained a sample of 29 manufacturing companies. The type of data used is quantitative data with secondary data sources. The data collection method used is the documentation method. The analytical technique used in this study is descriptive analysis, classical assumptions, multiple linear regression, and hypothesis testing with the help of SPSS Version 25 software. The independent variables used in this study are capital intensity, sales growth, and institutional ownership. The dependent variable used in this study is tax avoidance. The results of the study show that partially, the capital intensity variable has a significant negative effect on tax avoidance, the sales growth variable has a positive and significant effect on tax avoidance, and the institutional ownership variable has a positive and significant effect on tax avoidance, and simultaneously shows that all independent variables have a positive effect and significant to the dependent variable.